Association Between Exercise and Blood Glucose Levels In Diabetic Patients - Eryna Laili Putri (Jurnal Berkala Epidemiologi, 2016)
Diabetes Mellitus (DM) is a chronic disease with a high prevalence. Physical exercise is an important activity carried out routinely by people with DM in order to maintain the stability of blood glucose levels. The purpose of this study was to determine the relationship of physical exercise categorized by the frequency, duration, and intensity of physical exercise with the average random blood glucose level in patients with DM. This research is an observational analytic study with a case-control design. This research was conducted at the Public health center (PHC) of Pacar Keling, Surabaya in 2015. Data were obtained from interviews conducted in 20 case group samples and 20 control group samples with a systematic random sampling technique. The dependent variable in this study was the mean random blood glucose level, while the independent variables were frequency, duration, intensity, and type of physical exercise. This study used a Chi-Square test. The results showed that physical exercise factors related to the average random blood glucose level were duration of physical exercise (p = 0.022) and intensity of physical exercise (p = 0.021). The frequency of physical exercise was not related to the average random blood glucose level (p = 0.340). DM patients who do not do physical exercise run the risk of having an average of uncontrolled random blood glucose levels. The conclusion of this study is the total duration and intensity of physical exercise related to the average random blood glucose level. A physical exercise carried out 3 times 30 minutes per week can reduce the risk of uncontrolled blood glucose levels.